Аналіз прес форм гнучких роботів - Філіппов, І. Ю. (ХНУРЕ, 2019)
Soft robotics has become increasingly popular in many applications from auxiliary medical devices to industrial production facilities. One of the areas in which soft robotics has a significant impact is to develop soft grips and manipulators. The principle of soft capture is aimed at the use of soft pneumatic actuators (SPA). The basic method for developing the required mold for soft capture is the Finite Element Method (FEM).
Keywords: soft robotics; soft pneumatic actuators; Finite Element Method